Prognostic impact of adjuvant chemotherapy in high-risk nasopharyngeal carcinoma patients. (January 2017) - Liu, Yi-Chun; Wang, Wen-Yi; Twu, Chih-Wen; Jiang, Rong-San; Liang, Kai-Li; Wu, Ching-Te; Lin, Po-Ju; Huang, Jing-Wen; Hsieh, He-Yuan; Lin, Jin-Ching
Highlights: Adjuvant chemotherapy (AdjCT) reduced relapse in high-risk nasopharyngeal cancer patients. AdjCT significantly improved both overall survival and progression-free survival. The risk-features guided approaches are feasible during daily practice in all hospitals. Abstract: Objectives: To investigate the prognostic impact of adjuvant chemotherapy (AdjCT) in patients with high-risk nasopharyngeal carcinoma (NPC). Materials and methods: A total 403 NPC patients with at least one of the following criteria (1) neck node > 6 cm; (2) supraclavicular node metastasis; (3) skull base destruction/intracranial invasion plus multiple nodes metastasis; or (4) multiple neck nodes metastasis with one of nodal size > 4 cm were retrospectively reviewed. All patients finished curative radiotherapy ± neoadjuvant/concurrent chemotherapy. Post-radiation AdjCT consisted of tegafur-uracil (two capsules twice daily) for 12 months. We analyzed the treatment outcome between patients with (n = 154) and without (n = 249) AdjCT. Results: Baseline patient characteristics at diagnosis (age, gender, pathological type, performance status, T-classification, N-classification, and overall stage) were comparable in both arms. After a median follow-up of 72 months for surviving patients, 31.8% (49/154) and 42.2% (105/249) in patients with and without AdjCT developed tumor relapse respectively (P = 0.0377). AdjCT improved both overall survival (HR 1.89, 95% CI 1.37–2.61, P  = 0.0001) and progression-free survival (HR 1.42, 95% CI 1.03–1.96, P  = 0.0322). There were significant reduction in distant failures ( P  = 0.0016) but not in local ( P  = 0.8587) or regional ( P  = 0.8997) recurrences for patients who received AdjCT. Conclusion: AdjCT can reduce distant failure and improve overall survival in high-risk NPC patients after curative radiotherapy ± neoadjuvant/concurrent chemotherapy.